Emergence of joint health and safety committees in Algerian companies: an exploratory study - Bousfot, Widad; Saadi, Saadia; Djebabra, Mébarek (International Journal of Health and Governance, 2022)
Purpose The objective of this article is to carry out an exploratory study on the emergence of health and safety committees (HSC) in Algerian companies. Design/methodology/approach The methodology chosen, governed by the systemic approach, is centered on the exploration of HSC emergence factors in companies. Findings The suggested method consists in defining hypotheses found in the literature on the emergence of HSC in order to affirm or refute them in the case of Algerian companies. Research limitations/implications Despite the fact that a good number of Algerian industrial companies were solicited; the number of respondents was limited. This limitation confirms the difficulty commonly encountered in exploratory studies by questionnaire. Practical implications The results of this exploratory study serve as a basis for the elaboration of a national action plan dedicated to HSC emergence in Algerian companies. Originality/value This is the first study conducted in Algerian companies on HSC emergence. The identification of emergence problems allows drawing up an effective action plan to solve them.